Structural framework, operational dysfunctions, and position of the European Union and its Member States regarding the sanctions adopted against the Russian Federation in connection with the invasion of Ukraine - Puerta Domínguez, Enrique Manuel (2025)
The outbreak of the Russian-Ukrainian war was an unexpected shock that caused so much upheaval that it represented a historic turning point in several fields. There are those who assume that February 24, 2022 symbolically marks the end of the political cycle, which lasted thirty years, in which we seemed to have left behind the era of the hot war in Europe. Some perceive this as a regression in evolution in which, despite diplomatic efforts, avoiding armed conflict has proven unattainable. In the old continent there has been a reappearance of “power politics” that has caused what we could call a “tectonic shift in European history.” This contribution analyzes the various complex structures that come into play on the European board, and that must begin according to the very complexity of the EU framework, not only difficult to understand for other nations, but for the citizens of the old continent themselves.